Clinical significance of interleukin-18 and interleukin-10 in patients with chronic obstructive pulmonary disease combined with hypertension - Melenevych, A. Ya. (Zaporozhye Medical Journal, 2018)
The problem of chronic obstructive pulmonary disease (COPD) in combination with hypertension (HT) is becoming more relevant because of the growth of its prevalence and adverse consequences in the world as well as in Ukraine. Aim: To assess the level of interleukin-18 (IL-18) and IL-10 in patients with COPD in combination with HT. Materials and methods. We examined 87 patients with occupational COPD GOLD 2–3, groups B, C, D. The main group included 67 patients with COPD in combination with HT stage II, the comparison group – 20 patients with COPD. Patients were divided into phenotypes: emphysematous, chronic bronchitic, frequent exacerbator and asthma-COPD overlap syndrome (ACOS) based on the analysis of clinical and anamnestic, anthropometric, spirometric data and chest X-ray examination. The examination was carried out in remission which is characterized by stable clinical symptoms and spirometry indices. General clinical and laboratory examinations, pulse oximetry, pulmonary function test, electrocardiographic, echocardiographic and chest X-ray examinations were performed in all patients. IL-18 and IL-10 in peripheral blood were determined by ELISA using a test system “Bender MedSystems, GmbH” (Austria). The control group included 20 practically healthy age- and gender-matched persons. Statistical analysis of the data was performed using nonparametric statistical methods. The probability of differences in independent groups was estimated using the Mann-Whitney U-criterion. All statistical tests were bilateral, differences were considered significant for P < 0.05. Results. Analysis of IL-18 levels in patients of the main group, comparison group and control group showed statistically significant differences. The most significant increase in IL-18 level was observed in patients of the main group that was associated with more severe systemic inflammation in COPD combined with HT. The level of IL-10 was significantly increased only in the main group. Patients with COPD GOLD 3, groups C, D and COPD GOLD 2, group B did not significantly differ in IL-18 and IL-10 levels, but there was a tendency to decrease in IL-18 and increase in IL-10 levels in patients with COPD GOLD 3, groups C, D due to initial manifestations of IL-18-mediated proinflammatory response exhaustion. Significant differences between levels of IL-18 and IL-10 in patients with COPD with different phenotypes were revealed. IL-18 levels were elevated in all studied patients, but the degree of increase was quite different. Frequent exacerbators demonstrated blunted IL-18-mediated proinflammatory and excessive anti-inflammatory response. Conclusions. Cytokine imbalance in patients with COPD in combination with HT determines the course of disease and may be a prognostically significant criterion for consequences of the disease.